A comparative study of some educational values for practitioners and non-practitioners of physical activities and sports in the physical education class: A field of study of some secondary schools in Djelfa Province, Algeria - - Abderahmen, Lakehal; Fairouz, Azaiz (Journal of Educational and Psychological Sciences, 2020)
This study aimed to know the level of educational values among pupils in the first grade of secondary school, comparing the educational values of practitioners and non-practitioners of physical and sports activities in the physical education quota. The researcher also conducted a study on a sample of 100 elements. Study Tools: The researchers used the following tool: the 35-paragraph value scale prepared by Jaber Abd Rabbo and directed to students, and the researcher used the descriptive analytical method in the study, while the statistical methods were as follows: mathematical average, repetitions, standard deviation, test T, where the results of the study were the value of the calculated stod, which was 3.29, which was greater than the table, which was 1.96. The results of the study revealed that the level of values among pupils in the first grade of secondary school was high, and showed that there were differences between practitioners and non-practitioners of physical activity in the share of physical education in educational values. The researchers also recommended attention to the practice of physical and sports education and urged all students to do so, as well as to involve parents in the matter and their awareness about their children’s physical education, with the need for teachers to pay attention to values from the mental and psychological aspects of students, which in turn develop values in various fields.